Internet dalam Konteks Perpustakaan - Rodhin, Roni (STAIN Ponorogo, 2012)
The presence of internet would bring a variaty of effects in all areas of human life. The impac of bias could be both a positive and negative. On the other side for libraries it would bring a disparate impact, engagedÂ in the service and information. In the contect of libraries, the internet is very helpfull to disseminate information that is available in it. It means internet becomes a partner in the dissemination of information. Therefore, the existence of internet is very important for the library.